Strategies for PET imaging of the receptor for advanced glycation endproducts (RAGE) - Lindsey R. Drake; Allen F. Brooks; Jenelle Stauff; Phillip S. Sherman; Janna Arteaga; Robert A. Koeppe; Aimee Reed; Timothy J. Montavon; Marc B. Skaddan; Peter J.H. Scott (Elsevier, 2020)
The implication of the receptor for advanced glycation end-products (RAGE) in numerous diseases and neurodegenerative disorders makes it interesting both as a therapeutic target and as an inflammatory biomarker. In the context of investigating RAGE as a biomarker, there is interest in developing radiotracers that will enable quantification of RAGE using positron emission tomography (PET) imaging. We have synthesized potential small molecule radiotracers for both the intracellular ([18F]InRAGER) and extracellular ([18F]RAGER) domains of RAGE. Herein we report preclinical evaluation of both using in vitro (lead panel screens) and in vivo (rodent and nonhuman primate PET imaging) methods. Both radiotracers have high affinity for RAGE and show good brain uptake, but suffer from off-target binding. The source of the off-target PET signal is not attributable to binding to melatonin receptors, but remains unexplained. We have also investigated use of lipopolysaccharide (LPS)-treated mice as a possible animal model with upregulated RAGE for evaluation of new imaging agents. Immunoreactivity of the mouse brain sections revealed increases in RAGE in the male cohorts, but no difference in the female groups. However, it proves challenging to quantify the changes in RAGE due to off-target binding of the radiotracers. Nevertheless, they are appropriate lead scaffolds for future development of 2nd generation RAGE PET radiotracers because of their high affinity for the receptor and good CNS penetration.